Lack of association between the GNB3 rs5443, HIF1A rs11549465 polymorphisms, physiological and functional characteristics. (11th May 2020) - Bosnyák, Edit; Trájer, Emese; Alszászi, Gabriella; Móra, Ákos; Györe, István; Udvardy, Anna; Tóth, Miklós; Szmodis, Márta
Abstract: The aim was to examine the association between the hypoxia‐inducible factor‐1α (HIF1A) gene and the guanine nucleotide binding protein beta polypeptide 3 (GNB3) gene polymorphisms and the endurance/power athlete status and relative aerobic capacity. Another goal of this study was to reveal the connection between GNB3, blood pressure (BP), body composition and body mass index (BMI). Two hundred thirty‐eight people participated in this study: 148 elite athletes (men = 107, women = 41) and 90 controls (men = 51, women = 39). The athletes were divided into two groups: the power and the endurance athletes. BMI and body fat percentage (fat%) were calculated. Fifty of the athletes underwent an incremental treadmill test to exhaustion; BP was monitored before and after the test. There were differences in the genotype frequencies of HIF1A between the endurance and the control group (ProPro: 64% vs.79%, ProSer: 27% vs.19%, SerSer: 9% vs. 2%; p = .0351); in the allele prevalences among the three groups (Pro: 87% vs. 77% vs. 88%; Ser: 13% vs. 23% vs. 12%; p = .0103) and between the endurance and control group ( p = .0049) as well. The GNB3 allele proportions differed in the three groups (C: 74% vs. 61% vs. 71%, T: 26% vs. 39% vs. 29%; p = .0436). There were no connections between the genotypes and the relative aerobic capacity and neither between GNB3 genotypes and BP, BMI and fat%. The connection of GNB3 T allele to the endurance performance still remained contradictable.